A Tinjauan Etika dan Komunikasi Konsultasi Refraksi: Perspektif Pasien dan Praktisi - Lathifa, Meisya Miftha; Sihombing, Cindy Agustine Naomi; Syifa, Nadya Ulya; Neza, Rawsyan Alfan; Angeli, Thea Mervella; Lumentut, Raffael Merdnard; Yen, Liauw Djai (Universitas Kristen Krida Wacana, 2025)
Refractive consultation is not only a technical process of determining vision correction, but also involves interpersonal interactions between practitioners and patients that include aspects of communication as well as ethical values. Non-empathic communication can lead to misunderstanding and lower patient trust in the service. This study aims to examine the role of communication and ethical approach to care. This study used the literature review method by searching relevant scientific publications from 2014-2024. Primary sources were analyzed ethical values, and the views of patients and optometry practitioners. Data synthesis was conducted through content analysis to summarize key issues and identify gaps that need further research. The results showed that clinical communication and the application of ethical principles such as autonomy, justice, beneficence, and non- maleficence play an important role in building trust and improving service quality. However, obstacles in the field, such as time constraints, high patient numbers, and lack of communication training in ethics that make interactions less empathetic. A review of the literature shows the importance of empathy, clarity of information, and responsiveness in clinical interactions to improve satisfaction and quality of care.